Hubungan Pencahayaan dengan Kelelahan Mata pada Pekerja Taylor - Muhammad Amin; Winti Winiarti; Panzilion Panzilion (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
This study aims to determine the relationship between lighting and eye fatigue of workers Indah Taylor and Duta Taylor in Bengkulu City in 2017. The type of research used is descriptive analytic with a cross sectional approach. The results showed that of the 30 respondents, as many as 8 respondents (26.7%) had lighting that met the standards, as many as 22 people (73.3%) had lighting that did not meet the standards. Of the 30 respondents, 20 respondents (66.7%) %) who were declared tired, 10 (33.3%) respondents were not tired. The results of the bivariate analysis showed that the value of p = 0.000. In conclusion, there is a significant relationship between lighting and eye fatigue for Indah Taylor and Duta Taylor in Bengkulu City in 2017. Keywords: Eye Fatigue, Lighting, Tailor